Improving the properties of unburned earth to control the interior microclimate - Michal Procházka; Zbyněk Zušťák; Pavel Svoboda (Acta Polytechnica CTU Proceedings, 2022)
The article concerns the problematics of unburned earth used as material for moulding formwork or clay plaster with lowered contraction, especially about interior unburned earth plaster with the heightened percentage of clay and therefore improved sorption abilities. By adding a plasticizer, it is possible to modify the fluidity of the mixture. With lessening the amount of water it is possible to lower the shrinkage. Furthermore, we can increase the ratio of clay to sand and thus we can control the indoor microclimate. This is because the clay provides adsorption properties. Unburnt clay has been widely used as a building material in the past around the world. In the last century, this material was rather despised. Nowadays, however, this trend is reversing and the unburnt clay is experiencing a renaissance. Increasingly people emphasize ecology, a healthy and balanced indoor climate, and demand buildings with low operational and energy intensity. All this can be offered by unburnt clay, because it is energy-efficient in production, easily accessible in almost all parts of the world, harmless, and beneficial to human health, as clay can contribute to the improvement of the internal microclimate to a much greater extent than other building materials, as confirmed by many scientific findings.